Manajemen Pariwisata Berkelanjutan dalam Pengelolaan Pura Maduwe Karang di Desa Kubutambahan, Kabupaten Buleleng - Ketut Rediyasa; I Nengah Lestawi; Ida Ayu Tary Puspa (Semantik : Jurnal Riset Ilmu Pendidikan, Bahasa dan Budaya, 2026)
The fundamental issue in sustainable tourism management that remains less than optimal can be seen from the limited involvement of local communities and the lack of integrated management of tourism potential in the Pura Maduwe Karang area. The purpose of this study is to analyze sustainable tourism management in the management of Pura Maduwe Karang. This research employs a qualitative approach with a case study method through observation, interviews, literature review, and documentation. The theoretical foundations used include the concepts of Sustainable Tourism, the Triple Bottom Line, and Tourism Impact Theory.The results show that the implementation of sustainable tourism management at Pura Maduwe Karang is still basic and has not been structured professionally. The socio-cultural aspect is relatively well preserved through customary roles and ceremonial activities; however, the economic aspect has not provided significant benefits for individuals in the local community, as contributions remain limited to collective interests of the traditional village. The environmental aspect is currently well maintained due to the temple’s sacred status but may decline if tourist numbers increase without proper management. The main constraints lie in the lack of promotion, facilities, and human resource capacity in management. This study emphasizes the importance of tourism management strategies that balance the dimensions of profit, people, and planet, and encourages collaboration among traditional villages, local governments, and communities to maintain the sustainability of the temple as both a cultural heritage site and a tourist destination.